TINGKAT PENGETAHUAN PASIEN TERHADAP VAKSINASI COVID-19 DI PUSKESMAS BAJENG KABUPATEN GOWA - Agust Dwi Djajanti; Sukirawati Sukirawati; Hernawati Basir (Jurnal Kesehatan Yamasi Makassar, 2022)
A study was conducted on "Patients' Knowledge Level of Covid-19 Vaccination at the Bajeng Health Center, Gowa Regency in July 2021". The purpose of this study was to obtain information about the patient's level of knowledge about the Covid-19 vaccination at the Puskesmas in July 2021. This type of research was a descriptive study using a questionnaire as a data collection instrument. The sample in this study was all people who wanted to vaccinate against Covid-19 and did not want to vaccinate against Covid-19 at the Bajeng Health Center, Gowa Regency, as many as 50 people. The results of the respondents' answers to the questionnaire given were then tabulated and scored and then presented. For the assessment category, the Guttman scale is used, namely the category of good knowledge with a range: 51 - 100% and low knowledge with a range: 0 – 50%. The results of this study can be concluded that 79% of patients know about the Covid-19 vaccination.